2007
DOI: 10.2217/17435889.2.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-Targeted Perfluorocarbon Nanoparticles for Targeted Thrombolysis

Abstract: This new nanoparticle-based thrombolytic agent provides specific and rapid fibrinolysis in vitro and may have a clinical role in early reperfusion during acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…This is achieved by concentrating the available drug at the desired site and permitting a lower systemic dose. A fibrin-specific, liquid perfluorocarbon nanoparticle that is surface modified to deliver the plasminogen activator streptokinase has been developed, which shows such characteristics [57]. Effective concentrations of targeted streptokinase were orders of magnitude lower than equivalently efficacious levels of free drug.…”
Section: Novel Ultrasound-mediated Drug Delivery Systems For Thrombolmentioning
confidence: 99%
“…This is achieved by concentrating the available drug at the desired site and permitting a lower systemic dose. A fibrin-specific, liquid perfluorocarbon nanoparticle that is surface modified to deliver the plasminogen activator streptokinase has been developed, which shows such characteristics [57]. Effective concentrations of targeted streptokinase were orders of magnitude lower than equivalently efficacious levels of free drug.…”
Section: Novel Ultrasound-mediated Drug Delivery Systems For Thrombolmentioning
confidence: 99%
“…Targeting of clotdissolving therapeutics could potentially decrease the frequency of complications at the same time as simultaneously increasing treatment effectiveness by concentrating the available drug at the desired site and permitting a lower systemic dose. 65 Any new system must be simple and safe when widely used. If safety can be proven even in hemorrhagic strokes, it may well be possible to use some technique of microbubble-augmented US lysis or US-augmented thrombolysis in patients who have not yet been transported to the hospital for CT to determine the presence or absence of intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Using plasminogen activators in nanoparticle constructs capable of targeting clots could prevent blockage. Marsh et al investigated the use of streptokinase linked to perfl uorocarbon nanoparticles targeted towards fi brin and showed that a 1000-fold dose of free streptokinase would be required to achieve the levels of lysing caused by the streptokinase-enabled nanoparticles [ 70 ]. Using a more complex nanoparticle construct, Erdem et al and McCarthy et al used CLIOs that target fi brin and activated factor XIII, which crosslinks with fi brin during clot formation.…”
Section: Nanomaterials For Cardiovascular Molecular Imagingmentioning
confidence: 99%